PENGARUH KUALITAS PRODUK KAKAO HARGA DAN SERVICE QUALITY TERHADAP MINAT BELI KONSUMEN DI UPT TTP NGLANGGERAN KABUPATEN GUNUNG KIDUL - Pralambang, Ramadhan Dino; Maharani, Artita Devi; Stefani, Eska (JURNAL ILMIAH AGRITAS, 2025)
This study aims to analyze the effect of cocoa product quality, price and service quality on consumer buying interest in UPT TTP Nglanggeran, Gunung Kidul. The basic research method is to use quantitative research with sampling techniques using lemeshow. The population in this study were consumers of UPT TTP Nglanggeran with a sample size of 100 respondents. The data analysis method used is multiple linear regression. The results of multiple linear regression analysis show that there is a significant partial effect on the product quality and price variables on consumer buying interest in UPT TTP Nglanggeran, while service quality has no partial effect on consumer buying interest in UPT TTP Nglanggeran. Based on the results of the simultaneous hypothesis test (F test), it shows that the independent variables simultaneously have a significant effect on the dependent variable (consumer buying interest). UPT TTP Nglanggeran needs to hold training on customer service to improve service quality.